Ground Penetrating Radar Survey Across The Bok Bak Fault, Kedah, Malaysia - Yuaniarti Ulfa; Nur Fathin Mohd Jamel; Mardiana Samsuardi (Pusat Teknologi Bahan Galian Nuklir - BATAN, 2013)
A ground penetrating radar (GPR) survey was done across the Bok Bak Fault zone in Baling, Kedah in order to investigate the shallow subsurface geology of the Bok Bak fault zone, its extension and associated weak zones within the study area. GPR data acquisition was compared with visual inspection on the slope of the outcrop. Ten GPR profiles were acquired using 250 MHz GPR frequency. Basic data processing and filtering to reduce some noise and unwanted signal was done using MALA RAMAC Ground Vision software. The data penetrate around 2 meters in depth for all survey lines. In most lines shows clear images of shallowest Bok Bak Fault (NW trending) as detected at distance of 28 m horizontal marker. It also exhibits several sets of faults as a result of Bok Bak Fault deformation, including the conjugate NE trending fault (Lubok Merbau Fault). Active seismicity encompasses the Malay-Thai Peninsular trigger the changes of Bok Bak Fault dipping direction, steeper dips of conjugate faults and faults or fractures rotational movement. Survei menggunakan ground penetrating radar (GPR) yang dijalankan melalui kawasan patahan Bok Bak di Baling, Kedah adalah bertujuan untuk menyelidiki geologi dangkal zona bawah tanah patahan Bok Bak, kemenerusannya beserta zona-zona lemah di sekitar patahan tersebut. Data pengukuran GPR yang diperoleh kemudian dibandingkan dengan hasil pengamatan langsung pada tebing singkapan. Sepuluh profil GPR telah diperoleh menggunakan frekuensi 250 MHz. Pemrosesan dasar dan penapisan data untuk mengurangi sinyal-sinyal yang tidak dikehendaki berikut gangguan-gangguan suara dilakukan dengan piranti halus MALA RAMAC Ground Vision. Data mampu menembus hingga kedalaman 2 meter untuk semua garis survei. Umumnya garis survei menunjukkan gambar yang jelas untuk patahan Bok Bak (ke arah Barat Laut) sebagaimana terdeteksi di jarak 28 m pada penanda horisontal. Beberapa set patahan yang dihasilkan dari deformasi patahan Bok Bak juga dapat dideteksi, termasuk pasangan patahan yang ke arah Timur Laut (patahan Lubok Merbau). Pergerakan aktif seismik di Peninsula Malaya-Thailand turut memicu perubahan arah kemiringan patahan Bok Bak, menjadikan kemiringan pasangan patahan lebih curam, dan pergerakan rotasi patahan dan retakan.